Association of Selected Antipsychotic Agents With Major Adverse Cardiovascular Events and Noncardiovascular Mortality in Elderly Persons. Issue 9 (September 2015) - Sahlberg, Marie; Holm, Ellen; Gislason, Gunnar H.; Køber, Lars; Torp‐Pedersen, Christian; Andersson, Charlotte
Abstract : Background: Data from observational studies have raised concerns about the safety of treatment with antipsychotic agents (APs) in elderly patients with dementia, but this area has been insufficiently investigated. We performed a head‐to‐head comparison of the risk of major adverse cardiovascular events and noncardiovascular mortality associated with individual APs (ziprasidone, olanzapine, risperidone, quetiapine, levomepromazine, chlorprothixen, flupentixol, and haloperidol) in Danish treatment‐naïve patients aged ≥70 years. Methods and Results: We followed all treatment‐naïve Danish citizens aged ≥70 years that initiated treatment with APs for the first time between 1997 and 2011 (n=91 774, mean age 82±7 years, 35 474 [39%] were men). Incidence rate ratios associated with use of different APs were assessed by multivariable time‐dependent Poisson regression models. For the first 30 days of treatment, compared with risperidone, incidence rate ratios of major adverse cardiovascular events were higher with use of levomepromazine (3.80, 95% CI 3.43 to 4.21) and haloperidol (1.85, 95% CI 1.67 to 2.05) and lower for treatment with flupentixol (0.54, 95% CI 0.45 to 0.66), ziprasidone (0.31, 95% CI 0.10 to 0.97), chlorprothixen (0.76, 95% CI 0.61 to 0.95), and quetiapine (0.68, 95% CI 0.58 to 0.80). Relationships were generally similar for long‐term treatment. The majority of agents were associated with higher risks among patients with cardiovascular disease compared with patients without cardiovascular disease ( P for interaction <0.0001). Similar results were observed for noncardiovascular mortality, although differences in associations between patients with and without cardiovascular disease were small. Conclusions: Our study suggested some diversity in risks associated with individual APs but no systematic difference between first‐ and second‐generation APs. Randomized placebo‐controlled studies are warranted to confirm our findings and to identify the safest agents.